2022
DOI: 10.1159/000526271
|View full text |Cite
|
Sign up to set email alerts
|

Neuromedin U Induces Activation of Peripheral Group 2 Innate Lymphoid Cells through the ERK Pathway in Allergic Rhinitis Patients

Abstract: <b><i>Introduction:</i></b> In allergic diseases, group 2 innate lymphoid cells (ILC2s) play critical roles. Neuromedin U (NMU), a highly conserved multifunctional neuropeptide, is secreted by cholinergic neurons and involved in asthma pathogenesis by amplifying lung inflammation driven by ILC2s. However, the precise effects of NMU on ILC2s in allergic rhinitis (AR) and related diseases remain unclear. <b><i>Methods:</i></b> A total of 15 patients with persistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…NMU cooperatively enhanced IL-5 and IL-13 expression through IL-33-dependent or IL-33-independent mechanisms ( 96 , 98 ). A recent study in AR patients demonstrated that NMU activates ILC2s, resulting in the upregulation of the inflammatory factors IL-5 and IL-13 rather than IL-33 in patients with AR, triggering a type 2 inflammatory response, which was inhibited upon ERK pathway blockade ( 99 ).…”
Section: Role Of Neuropeptides In Neuroimmune Communication In Armentioning
confidence: 99%
“…NMU cooperatively enhanced IL-5 and IL-13 expression through IL-33-dependent or IL-33-independent mechanisms ( 96 , 98 ). A recent study in AR patients demonstrated that NMU activates ILC2s, resulting in the upregulation of the inflammatory factors IL-5 and IL-13 rather than IL-33 in patients with AR, triggering a type 2 inflammatory response, which was inhibited upon ERK pathway blockade ( 99 ).…”
Section: Role Of Neuropeptides In Neuroimmune Communication In Armentioning
confidence: 99%